In vitro evaluation of potential interference of lokivetmab with protein electrophoresis and immunofixation - Apostolopoulos, Neoklis; Mitropoulou, Athanasia; Foerster, Gesine; Failing, Klaus; Moritz, Andreas; Mayer, Ursula (Tierärztliche Praxis Ausgabe K: Kleintiere / Heimtiere, 2021)
Objective In humans, misdiagnoses of monoclonal gammopathy after use of therapeutic monoclonal antibodies has been documented. This triggers concerns for similar misdiagnoses in animals treated with monoclonal antibodies. The aim of this study was to evaluate if lokivetmab interferes with serum protein electrophoresis and immunofixation electrophoresis in dogs.Material and methods Residual sera from 25 client-owned, healthy blood donor dogs from 2 veterinary hospitals in Germany were used. The residual sera were analysed with serum protein electrophoresis and immunofixation electrophoresis before and after being spiked with lokivetmab at a concentration of 10 µg/ml (corresponding to the mean peak serum concentration after a subcutaneous injection of 2 mg/kg lokivetmab).Results No monoclonal gammopathy was observed on serum protein electrophoresis and all proteins had a normal distribution pattern without any pathologic bands on immunofixation electrophoresis. The absolute γ-globulin values of spiked samples, however, were significantly higher than in the native sera although they remained within the reference interval. No other globulin fractions were significantly different.Conclusion and clinical relevance This study suggests that lokivetmab at a dose of 2 mg/kg is not detected as a monoclonal peak on serum protein electrophoresis or immunofixation electrophoresis, and thus is unlikely to lead to a misdiagnosis of other diseases that are characterised by monoclonal gammopathies.
Keywords: Atopy; dog; globulins; interleukin-31; gammopathy